PENERAPAN METODE DISCOVERY LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK - Kura, Djanuarius W. Mau; Mones, Anselmus Yata (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2023)
The purpose of this study was to determine the quality of the results and the quality of the process of applying the discovery learning method to PAK learning, which can improve learning achievement for Class XI MIA 1 students in the 2021–2022 academic year. We collect data through observation, tests, and documentation. The results of research in the field prove that the results of research in each cycle indicate that the application of the discovery learning method can improve student achievement. The ability of student achievement increases in each cycle, where in Cycle I the number of scores obtained is 1,849, the class average is 71.11%, and the class mastery is 23.01% in the sufficient category and has not yet reached the KKM. In Cycle II the number of scores was 2,084, the class average was 80.15%, and the class completeness was 80.11%, which were in the good category and had reached the KKM. According to the author, the discovery learning method is highly suitable for students in class XI, MIA 1, to learn Catholic religious education. Based on the results obtained by the author, there is an increase in students' learning achievement, which includes cognitive, affective, and psychomotor aspects of learning Catholic religious education using the discovery learning method. Students know the quality of the results and the process of applying this method.